Modeling myeloproliferative neoplasms: From mutations to mouse models and back again. Issue 3 (May 2017) - Morotti, Alessandro; Rocca, Stefania; Carrà, Giovanna; Saglio, Giuseppe; Brancaccio, Mara
Abstract: Myeloproliferative neoplasms (MPNs) are defined according to the 2008 World Health Organization (WHO) classification and the recent 2016 revision. Over the years, several genetic lesions have been associated with the development of MPNs, with important consequences for identifying unique biomarkers associated with specific neoplasms and for developing targeted therapies. Defining the genotype-phenotype relationship in MPNs is essential to identify driver somatic mutations that promote MPN development and maintenance in order to develop curative targeted therapies. While studies with human samples can identify putative driver mutations, murine models are mandatory to demonstrate the causative role of mutations and for pre-clinical testing of specific therapeutic interventions. This review focuses on MPN mouse models specifically developed to assess the pathogenetic roles of gene mutations found in human patients, as well as murine MPN-like phenotypes identified in genetically modified mice.